Formation of Suffite schools in the Balkans - Hauziński, Jerzy (Balcanica Posnaniensia. Acta et studia, 2001)
The article presents the origins and development of Sufism in the Balkans during the period of Ottoman expansion. The author analyzes the role of dervish orders (tariqas) in the processes of conquest, Islamization, and social integration within the region. The study employs a historical and religious approach based on Ottoman sources and literature concerning the history of Islam. The research demonstrates that Sufi communities played a significant role not only in spreading Islam but also in creating social bonds among populations of different ethnic and religious backgrounds. Particular attention is devoted to the Bedreddin movement and the development of Bektashism in Albania. The author emphasizes the importance of heterodox and syncretic currents that facilitated the adaptation of Islam to local cultural conditions. The conclusions indicate that the activities of Sufi orders constituted one of the most important factors shaping the religious and cultural distinctiveness of the Ottoman Balkans.